General characteristics valeological schooling primary school children - Дмитрук, В. С. (Slobozhanskyi Herald of Science and Sport, 2011)
The article presents the main aspects valeological schooling students. In a school, it is important to teach students to use the reserve forces of the organism, to teach to live in a society healthy person, build relationships, communicate with people, to foresee the consequences of his conduct, to be able to make timely decisions. Subjects physical education, valeology, life safety are as unit, which provides education and schooling of a healthy personality. Stressed the role of the precautionary principle as the fundamental system in valeological training.